Growth of Saccharomyces cerevisiae yeast cells under broadband light - Castañares, Michael Lawrence G. (National Institute of Physics, College of Science, University of the Philippines Diliman, 2014)
The growth of yeast exposed to laser beam and to LED light was observed under a microscope. Continuous exposure to light with irradiance (>3W/m2) for 120 mins inhibited the collective growth of yeast. A single cell was trapped using 632 nm dual beam optical tweezers. The cell budded towards either traps regardless of powerThe results would add insights on the use of visible light in photodynamic therapy.